Determinants of continuous intention on online food delivery applications from customers perspectives in Northern Region, Malaysia. - Abdul Nasir, Nur Syakinah; Abdull Rahman, Nurul Labanihuda; Abd Mutalib, Hasyeilla; Shafee, Mohd Imran Khusairi (International Journal of Accounting, Finance and Business, 2025)
Online food delivery (OFD) services are increasingly common in Malaysia. Many people are drawn to using OFD in their daily lives because of its benefits for customers. Consumers have the option of ordering food online and using a delivery service rather than doing so in person. People from all walks of life are able to order food with just one click from their gadgets in the information technology (IT) era. Moreover, online food delivery applications (OFDAs) are a new type of platform for the distribution of online-to-offline (O2O) services. The term "OFDAs" refers to a mobile service that enables quick and easy online ordering as well as offline delivery of goods and services. This paper seeks to study the determinants of continuous intention to use online food delivery applications from customers' perspectives in the Northern Region, Malaysia. A quantitative approach was used in this study. Questionnaires were used to collect the data from all respondents via Google Form. The respondents were customers from the Northern Region, Malaysia, who used online food delivery applications, with a sample size of 477 people. Therefore, Partial Least Squares (SmartPLS) have been used to evaluate the research data. Finally, this study can be applied and extended to determine the determinants of continuous intention to use online food delivery applications in other countries.